A case report of successful rescue using veno-arterial extracorporeal membrane oxygenation: managing cerebral-cardiac syndrome - Wang, Zheng; Zhang, Qi-Feng; Guo, Miao; Qi, Xiao-Xia; Xing, Xiao-Hui; Li, Gang; Zhang, Shuang-Long (Frontiers in Cardiovascular Medicine, 2024)
Introduction: The presence of cerebral-cardiac syndrome, wherein brain diseases coincide with heart dysfunction, significantly impacts patient prognosis. In severe instances, circulatory failure may ensue, posing a life-threatening scenario necessitating immediate life support measures, particularly effective circulatory support methods. The application of extracorporeal membrane oxygenation (ECMO) is extensively employed as a valuable modality for delivering circulatory and respiratory support in the care of individuals experiencing life-threatening circulatory and respiratory failure. This approach facilitates a critical temporal window for subsequent interventions. Consequently, ECMO has emerged as a potentially effective life support modality for patients experiencing severe circulatory failure in the context of cerebral-cardiac syndrome. However, the existing literature on this field of study remains limited. Case description: In this paper, we present a case study of a patient experiencing a critical cerebral-cardiac syndrome. The individual successfully underwent veno-arterial-ECMO (VA-ECMO) therapy, and the patient not only survived, but also received rehabilitation treatment, demonstrating its efficacy as a life support intervention. Conclusion: VA-ECMO could potentially serve as an efficacious life support modality for individuals experiencing severe circulatory failure attributable to cerebral-cardiac syndrome.